2014
DOI: 10.1039/c4cc04985c
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast electron injection at the cationic porphyrin–graphene interface assisted by molecular flattening

Abstract: The steady-state and femtosecond (fs) time-resolved data clearly demonstrate that the charge transfer (CT) process at the porphyrin-graphene carboxylate (GC) interfaces can be tuned from zero to very sufficient and ultrafast by changing the electronic structure of the meso unit and the redox properties of the porphyrin cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
105
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(112 citation statements)
references
References 36 publications
7
105
0
Order By: Relevance
“…[15][16][17][18] To further confirm the non-covalent association of ZnTMPyP with GC, the emission spectrum of a 5 mM aqueous solution of ZnTMPyP was measured after excitation at 563 nm in the presence of GC at different concentrations, as shown in Fig. The intensity of the Soret band shows a dramatic decrease upon addition of GC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18] To further confirm the non-covalent association of ZnTMPyP with GC, the emission spectrum of a 5 mM aqueous solution of ZnTMPyP was measured after excitation at 563 nm in the presence of GC at different concentrations, as shown in Fig. The intensity of the Soret band shows a dramatic decrease upon addition of GC.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 There have been a number of systems comprising noncovalent association of porphyrins with small molecules, 8,9 polymers, 10 DNA, 11 metallic nanoparticles, 12 and semiconductor quantum dots. 15 It has been demonstrated that fluorescence of the porphyrins was quenched upon interaction with GC due to electron or/and energy transfer. 15 It has been demonstrated that fluorescence of the porphyrins was quenched upon interaction with GC due to electron or/and energy transfer.…”
Section: Introductionmentioning
confidence: 99%
“…As there was no further interaction observed between CD and TMPyP after addition of 9 mM CD, we selected this concentration of CD for the further investigation with GC. 23 Hence, the estimated difference in efficiency can be related to the increased localization of electron density on the cavity of TMPyP and the ease of porphyrin oxidation in the TMPyP-b-CD complex compared to free TMPyP; this is evident from the change in oxidation potentials shown by the cyclic voltammetry measurements discussed below. As a result of complexation with b-CD, the observed spectral change in Soret band intensity can be attributed to the change in the local environment around the pyridinium unit.…”
Section: Introductionmentioning
confidence: 99%
“…[67][68][69][70] Because the dynamics of ground-state bleach recovery are directly proportional to the exciton depopulation, they are used as a convenient probe to determine the excited state dynamics including electron trapping and charge separation and recombination at materials surfaces and interfaces. After 350 nm of optical excitation, which was above the bandgap excitation, a clear ground-state bleach of approximately 500 nm corresponding to steady-state absorption was observed for the materials with a slight change in spectral features, as shown in Figure S9.…”
mentioning
confidence: 99%